PENERAPAN PENGELOLAAN KELAS BERBASIS STUDY GROUP DALAM PENINGKATAN ASPEK KETERAMPILAN BERBAHASA INDONESIA PADA SISWA SMP - Fadma Rosita; Apri Eka Budiyono; M. Rudi Gunawan Parozak (JURNAL ILMIAH GLOBAL EDUCATION, 2022)
The purposes of this study are 1) the researcher wants to analyze data about classroom management strategies in Indonesian subjects at MTs Jamiyatul Islamiyah, East Lombok. 2) describe the inhibiting factors and supporting factors for classroom management strategies, and 3) improving aspects of language skills. Then the researcher will carry out the applied research process which aims to draw policies. The research approach used is a qualitative descriptive approach. The object of this research is the Indonesian language teacher and the eighth grade students (8) totaling 26 students. Data collection techniques in qualitative research are interviews, observation, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing and testing conclusions. The results of this study are 1) classroom management has not been done well. Some teaching tools are incomplete and not available. 2) study groups are proven to work well and improve students' language skills. 3) there are several factors that inhibit and support the process of implementing the learning process using the study group method, including students feel unfamiliar with this method because it is the first time it has been done. Because of this, students are confused with concepts and the learning process. One of the supporting factors is the teacher who is interested and enthusiastic in practicing this method. 4) In the form of applied research conducted, the researcher suggests several things that schools need to do in order to improve school readiness for students. Some things that need to be done include planning for the procurement of equipment that is not yet available. In addition to the procurement of equipment, there needs to be training carried out by teachers in the learning process. Teachers need to have creative models and teaching methods. Schools also need to provide interesting supporting books to increase students' reading interest.